IMPROVING ADOLESCENT ANEMIA LITERACY THROUGH EDUCATION AND SCHOOL SCREENING - Priskila, Loury; Sira, Amaze Grace; Dinata, Fenita Renny; Wicaksono, Hendi (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2026)
Iron deficiency anemia remains a significant public health problem among adolescents in Indonesia, with evidence suggesting a persistent and increasing prevalence. Adolescent girls are particularly vulnerable due to increased iron requirements during rapid growth and menstrual blood loss, which may negatively affect cognitive performance, physical capacity, and future reproductive health. School-based interventions are therefore essential to strengthen early detection and prevention efforts. This community-based program aimed to promote adolescent health through hemoglobin (Hb) screening, nutritional status assessment, education on anemia and balanced nutrition, and the provision and monitoring of iron–folic acid supplementation. The activity was conducted in October 2025 at SMA Negeri 1 Imogiri, Bantul, involving 146 eleventh-grade students. A pre–post educational intervention design was applied. Data collection included Hb measurement using a portable Hb meter, anthropometric assessment (weight, height, body mass index, and arm circumfence), and a structured knowledge questionnaire. Knowledge levels increased from 62% before the intervention to 98% after the educational session, with a participant satisfaction rate of 97%. Several students were identified with low Hb levels and received follow-up support. This integrated, school-based approach demonstrates potential to improve health literacy and strengthen anemia prevention among adolescents.